MODIFICATION OF KELUD VOLCANIC ASH 2014 AS SELECTIVE ADSORBENT MATERIAL FOR COPPER(II) METAL ION - Susila Kristianingrum; Endang Dwi Siswani; Suyanta Suyanta (Jurnal Sains Dasar, 2016)
Abstract This research aims to prepare an adsorbent from Kelud volcanic ash for better Cu(II) adsorption efficiency than Kiesel gel 60G E'Merck. Adsorbent synthesis was done by dissolving 6 grams of volcanic ash activated 700oC 4 hours and washed with HCl 0.1 M into 200 ml of 3M sodium hydroxide with stirring and heating of 100 °C for 1 hour. The filtrate sodium silicate was then neutralized using sulfuric acid. The mixture was allowed to stand for 24 hours then filtered and washed with aquaDM, then dried and crushed. The procedure is repeated for nitric acid, acetic acid and formic acid with a contact time of 24 hours. The products were then characterized using FTIR and XRD, subsequently determined acidity, moisture content, and tested for its adsorption of the ion Cu (II) with AAS. The results showed that the type of acid that produced highest rendemen is AK-H2SO4-3M ie 36.93%, acidity of the adsorbent silica gel synthesized similar to Kiesel gel 60G E'Merck ie adsorbent AK-CH3COOH-3M and the water content of the silica gel adsorbent synthesized similar to Kiesel gel 60G E'Merck ie adsorbent AK-H2SO4-2 M. The character of the functional groups of silica gel synthesized all have similarities with Kiesel gel 60G E'Merck as a comparison. Qualitative analysis by XRD for all modified adsorbent showed a dominant peak of SiO2 except adsorbent AK-H2SO4 amorphous and chemical bonds with FTIR indicates that it has formed a bond of Si-O-Si and Si-OH. The optimum adsorption efficiency of the metal ions Cu(II) obtained from AK-H2SO4-5M adsorbent that is equal to 93.2617% and the optimum adsorption capacity of the Cu(II) metal ions was obtained from the adsorbent AK-CH3COOH-3M is equal to 2.4919 mg/ g. Keywords: adsorbents, silica gel, adsorption, kelud volcanic ash